Actinic keratosis: аctual view - T. V. Abramova; E. K. Murakhovskaya; Yu. P. Kovaleva (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The article summarizes information about the actinic keratosis. Presented data of the literature about the prevalence of the disease, the features of the clinical picture, diagnosis, differential diagnosis and treatment of dermatosis.